Low-Velocity Impact Behavior of Foam Core Sandwich Panels with Different Face Sheet Layers: Numerical and Experimental Study - Mohammad Amin Torabizadeh; Abdoulhossein Fereidoon (Mechanics of Advanced Composite Structures)
In this paper, some impact properties including maximum impact force, maximum displacement, specific absorbed energy, and failure mode of composite sandwich panels with aluminum foam core and different skin layers were investigated both numerically and experimentally. To compare the effect of different types of skin layers, in addition to the conventional aluminum layer, glass/epoxy composite with cross-ply and quasi-isotropic layouts was also employed. The experimental low-velocity impact tests were applied using a drop-weight device. All experimental tests were carried out based on the ASTM D7136. The finite element software, ABAQUS/Explicit, was employed to simulate the drop weight impact test of foam sandwiched composite. The finite element model was evaluated by comparing outputs between experimental results and the numerical simulation. Results showed that type of the face sheets and the fiber alignment in the composite surfaces significantly affected the impact behavior such as maximum impact force, failure mode, and absorbed energy. Based on the output results, the composite sheets with a quasi-isotropic skin layer had the highest specific absorbed energy. Moreover, in numerical results, the destruction area indicated more symmetry compared to the experimental ones. Also, the penetration depths of the impactor were completely dependent on the stacking sequence and type of top layer.